An immunomodulatory photosensitizer-mediated photodynamic therapy synergizes with PD-L1 blockade against metastatic triple-negative breast cancer - Liu, Yuetong; Wang, Liming; Kong, Feiyan; Liu, Tianjun; Liu, Hong (Frontiers in Pharmacology, 2025)
The clinical potency of anti-programmed death-ligand 1 (PD-L1) therapy in metastatic triple-negative breast cancer (TNBC) is modest primarily because of the intrinsic low immunogenicity and an immunosuppressive tumor microenvironment (TME). Photodynamic therapy (PDT), an inducer of immunogenic cell death (ICD), has the potential to enhance antitumor immune response and improve PD-L1 blockade efficacy. DTP, a novel photosensitizer developed previously, has demonstrated potent ROS-dependent photocytotoxicity, yet its immunomodulatory effects remain unexplored. This study investigated the induction of ICD and dendritic cell (DC) maturation following DTP-PDT in vivo and in vitro. A bilateral TNBC model was developed to assess the efficacy of DTP-PDT combined with α-PD-L1 therapy on untreated distant tumors and to explore its potential immunological mechanisms. The results showed that DTP-PDT effectively induced ICD, demonstrated by calreticulin membrane exposure, high mobility group box 1 protein release, and increased secretion of interferon-γ and tumor necrosis factor-α, resulting in DC maturation. The combination of DTP-PDT and α-PD-L1 significantly inhibited distant tumor growth. This effect was associated with increased CD8+ and CD4+ T cells infiltration, and reduced numbers of regulatory T cells, in the distant tumor and spleen. In conclusion, DTP-PDT enhanced TNBC sensitivity to α-PD-L1 by inducing ICD, and its combination withα-PD-L1 could remodel the immunosuppressive TME and enhance systemic immunity, resulting in a therapeutic effect against distant metastasis. This study provides experimental validation for a combined strategy of DTP-PDT and α-PD-L1, proposing a potential therapeutic approach for metastatic TNBC.